2021
DOI: 10.1111/1759-7714.14162
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary bypass does not consequentially contribute to postoperative distant metastasis of giant refractory thoracic tumors: A retrospective study with long‐term follow‐up

Abstract: Background Few clinical research studies with long‐term follow‐up have revealed whether cardiopulmonary bypass (CPB) increases the risk of postoperative distant metastasis in patients with giant refractory thoracic tumors. The present study evaluated the risk of distant metastasis after surgery utilizing CPB with long‐term follow‐up. Methods Clinical data for patients with giant refractory thoracic tumors who underwent resection with the use of CPB in the Second Affiliated Hospital of Soochow University during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Studies have shown that using CPB does not appear to increase the risk of tumor dissemination. For patients with locally advanced cancers, CBP can safely help remove the tumor and improve the survival to a certain extent ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that using CPB does not appear to increase the risk of tumor dissemination. For patients with locally advanced cancers, CBP can safely help remove the tumor and improve the survival to a certain extent ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tønnesen's study demonstrated that extracorporeal circulation inhibits the cytotoxic function of natural killer (NK) cells against tumor cells and causes a decrease in complement, lymphocytes, and neutrophils [24]. Chen and colleagues [25] found that extracorporeal circulation was acceptable for the risk of distant metastases after complete resection of thoracic malignancies in 14 cases of massive thoracic tumors resected under extracorporeal circulation with long-term follow-up. In addition, several reports comparing on-pump and off-pump CABG in cancer patients have shown no significant major adverse effect of extracorporeal circulation on cancer recurrence and late-stage survival [10,11,26].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports exist regarding the complete resection of TETs with aortic or cardiac invasion using cardiopulmonary bypass, yielding relatively favorable outcomes ( 46 - 48 ). The risk of systemic dissemination of tumor cells while employing cardiopulmonary bypass is deemed acceptable and seems to be low when juxtaposed with the risk of hematogenous tumor cell dissemination triggered by vascular invasion of malignant thymoma or thymic carcinoma ( 49 , 50 ).…”
Section: Combined Resection Of Surrounding Organs and R0 Resectionmentioning
confidence: 99%